Implementasi Komunikasi Organisasi dalam Kegiatan Dakwah untuk Memperbaiki Diri Narapidana di Lembaga Pemasyarakatan Kelas IIB Lumajang - Moh. Muafi Bin Thohir; Syamsul Hadi HM (Institut Agama Islam Syarifuddin Lumajang, 2020)
Da'wah has been going on for a long time among inmates in prison. Preaching took place at that place for a long time, namely during the Dutch government around 1917. After Indonesia's independence, the da'wah among prisoners was increasingly enhanced until now. The correctional system can be briefly said as a process of fostering prisoners based on a noble soul, and therefore also regards Prisoners as fellow creatures of God, individuals and members of the community. And in fostering prisoners, their mental life (including their religious life), physical and social life must be developed. With the correctional system, which means a renewal of the system in order to foster a complete human being, it is very necessary to have the right da'wah method, in accordance with and in tune with the correctional system. Penitentiary (Lembaga Pemasyarakatan) is a place to carry out guidance for prisoners and correctional students. Organizational communication is needed to carry out maximum coaching activities to achieve a goal and service that is satisfying for prisoners, as well as being a safe, orderly, free of extortion, drug and cell phone institution. Dai who was given the mandate at Lumajang Class IIB Correctional Institution had fulfilled the criteria of both scientific potential and personality potential so that the method used was in accordance with the madami faced by the prisoners who mostly inhabited the Class IIB Correctional Institution in Lumajang were drug cases. The average drug case is adolescence. The clerics always emphasize lectures on efforts to improve themselves both in the field of skills and personal because it is feared that after leaving the Lumajang Class II Correctional Institution unable to do something that can fulfill life. The challenge faced is the lack of seriousness of prisoners participating in the da'wah activities carried out by the Lumajang Class II Correctional Institution. This is due to prisoners having a level of memory that is tired because of drug addiction. Keywords: Da'wah, Organizational Communication, Penitentiary